2022
DOI: 10.1186/s12916-022-02501-2
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year trends in racial and ethnic enrollment in large diabetes randomized controlled trials

Abstract: Background: Lack of representativeness in Black, Indigenous, and People of Colour (BIPOC) enrollment could compromise the generalizability of study results and health equity. This study aimed to examine trends in BIPOC groups enrollment in diabetes randomized controlled trials (RCTs) and to explore the association between trial factors and high-enrollment of BIPOC groups. Methods:We systematically searched the literature on large diabetes RCTs with a sample size of ≥ 400 participants published between 2000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The increasing overall trend in participation we observed in this population-based observational study aligns with several recent systematic reviews on diabetes, heart failure, and cancer trials reporting increasing Latinx participation over the past decades or so [ 9 , 25 , 27 ]. However, our results contradict the widely accepted notion that participation rates declined in observational epidemiologic studies [ 20 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increasing overall trend in participation we observed in this population-based observational study aligns with several recent systematic reviews on diabetes, heart failure, and cancer trials reporting increasing Latinx participation over the past decades or so [ 9 , 25 , 27 ]. However, our results contradict the widely accepted notion that participation rates declined in observational epidemiologic studies [ 20 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…Further, although it has been widely reported that participation in observational epidemiological studies has decreased over the past several decades [ 20 24 ], none of these studies showed ethnic-specific time trends in participation. Other studies on historical trends in ethnic differences in participation all focused on clinical trials and had mixed findings on trends in the Latinx participation, with some reporting persistent or worsening underrepresentation, others presenting increased representation over time, and all lacking data clarifying whether the changes in representation resulted from changes in eligibility, access to clinical research, or willingness to participate, or a mixture of those [ 9 , 10 , 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that genetic polymorphisms can affect responses to vaccines [ 34 ] and medicinal therapeutics, such as antihypertensives, heart failure medications and warfarin [ 35 ]. Interventions which have been predominantly tested in White populations may not be as effective in other ethnicities [ 20 , 36 ], and indeed a lack of representation in trials for vaccines and therapeutics fuels mistrust and vaccine hesitancy amongst minority communities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the representativeness, equity and inclusivity of pulmonary rehabilitation across individual characteristics, and therefore health inequalities, are unknown. Furthermore, more evidence is needed to determine whether the intervention is equally effective across all characteristics [ 107 , 108 ]. To address this, the collection of data is vital [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Underrepresentation of ethnic minority groups has also been reported in cardiovascular disease [ 107 , 126 ], diabetes [ 127 ] and coronavirus disease 2019 (COVID-19) [ 128 , 129 ] research. However, if an intervention has been assessed in participants who are predominantly White British, it cannot be assumed that it will be equally effective across all other ethnicities [ 107 , 108 ]. Furthermore, reduced representation of ethnic minority groups in trials has been found to have wider implications, such as reduced trust and uptake of COVID-19 vaccines in ethnic minority groups [ 130 ], which may apply to other interventions or services, such as pulmonary rehabilitation.…”
Section: Discussionmentioning
confidence: 99%